Termite Inquilinism: proximate mechanisms mediating coexistence - Clemente, Lara Oliveira (2023)
Termite Inquilinism: proximate mechanisms mediating coexistence. Adviser: Og Francisco Fonseca de Souza. Co-advisers: Judith Korb and Rebecca Rosengaus Symbiosis, the long-term intimate relationship between different organisms, is ubiquitous. Understanding the proximate mechanisms that enable symbiosis can advance understanding of the evolutionary history of species and origins of biodiversity. The symbiotic system composed of the host termite species Constrictotermes spp and the inquiline termite species Inquilinitermes spp is a good working model for such studies, since several patterns and mechanisms mediating this cohabitation are already known. However, the invasion stage is less understood and interesting questions remain open. In this work we investigated the context of host nest invasion by inquilines from two approaches: mechanical and physiological. The results show correlations between the ontogeny of hosts and the positioning of their nests with the presence of inquilines, reinforcing the diversity of mechanisms mediating this symbiotic relationship. Keywords: Symbiosis, Isoptera, Physiology, Social Insects, Cohabitation